Physical exercise at term for enhancing the spontaneous onset of labor: a randomized clinical trial. (16th February 2022) - Pereira, Isabel Barros; Silva, Rita; Ayres-de-Campos, Diogo; Clode, Nuno
Abstract: Introduction: Physical exercise at term is empirically used as a method of enhancing the spontaneous labor onset. The objective of this study was to evaluate the effect of controlled maternal physical exercise at term as a method of enhancing the spontaneous labor onset. Materials and methods: At 38 weeks low-risk pregnant women, with a singleton cephalic fetus and no previous cesarean deliveries were randomly allocated to one of two arms: the experimental group performed 30 min of walking 3 times a week at 4 km/h, and the control group maintained their usual work and household activities. The primary outcome measure was the rate of labor induction. A sample size of 60 per group was planned to detect a 10% difference in labor induction rate, at a significance level of 0.05 and a power of 0.80. Results: The exercise group had a lower rate of labor induction (17.5 versus 33.3%, adjusted odds ratio [OR] = 0.28, 95% confidence interval [CI]; 0.14–0.87) and fewer operative vaginal deliveries (20.6 versus 38.1%, adjusted OR = 0.42, 95% CI; 0.17–0.92). No differences were found in gestational age at onset of spontaneous labor, duration of the active phase of labor, interval between induction and the active phase of labor, cesarean section rates, birth weight, and Apgar scores. No maternal or fetal heart rate abnormalities were recorded during the exercise sessions. Conclusions: For low-risk women at term walking for 30 min 3 times a week at 4 km/h from 38-week onwards is safe, enhances the spontaneous onset of labor and reduces operative vaginal delivery rates. Key Message: Physical exercise at term is empirically used as a method of enhancing the spontaneous labor onset. In finding that for low-risk women walking for 30 min 3 times a week at 4 km/h from 38-week onwards enhances spontaneous labor onset of and reduces operative vaginal delivery. Clinical Trial Registration: ClinicalTrials.gov . www.clinicaltrials.gov NCT02460185